Increase in environmental safety of system of current collecting of electric elevated transport - K. S. Markelova; O. A. Sidorov; V. M. Philippov (Омский научный вестник)
The article presents the advantages of the available types of elevated electric transport. The conditions have been indicated for ensuring reliable, economical and environmentally current of collection by electric transport. The results of experimental studies are published of negative factors of current collecting in real conditions of operation of elevated electric transport. The methods are considered that increase the environmental safety of current-collecting. The description is given of the best designs current of collectors with excellent environmental specifications.